miR-140-3p Inhibits Cutaneous Melanoma Progression by Disrupting AKT/p70S6K and JNK Pathways through ABHD2 - He, Yuanmin (Mol Ther Oncolytics, 2020)
Because cutaneous melanoma (CM) is one of the most lethal human tumors, major treatment advances are vital. miR-140-3p has been suggested to act as a suppressor in a range of malignant tumors, implying its possible use as a biomarker for effective antineoplastic treatment. However, the potential role of miR-140-3p in CM and the underlying mechanism remain unclear. In the present study, we identified lower levels of miR-140-3p in both CM tissues and cell lines; this downregulation was strongly associated with worse CM survival. Additionally, overexpression of miR-140-3p significantly inhibited cell proliferation, migration, and invasion in CM cells with different cell line origins. Importantly, by means of both bioinformatics analysis and luciferase reporter assay, we revealed abhydrolase domain containing 2 (ABHD2) to be a target of miR-140-3p in CM cells. Upregulation of ABHD2 reversed the tumor-suppressive effects of miR-140-3p in CM cells. Furthermore, miR-140-3p-targeted ABHD2 played a role in both activation of JNK signaling and inhibition of the AKT/p70S6K pathway in CM cells. Finally, in vivo results strongly suggested the suppressive effects of miR-140-3p on CM growth and metastasis. Collectively, our findings highlight a novel antineoplastic function for miR-140-3p in CM through ABHD2.